Penerapan Metode Rational Unified Process (RUP) Dalam Pengembangan Sistem Informasi Medical Check Up Pada Citra Medical Centre - Ririn Perwitasari; Royana Afawani; Sri Endang Anjarwani (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Mataram, 2020)
The Rational Unified Process (RUP) method is an iterative and incremental software development method that focuses on architecture. The RUP method will be used in the development of a medical check-up information system on a Citra medical center because this method is proactively able to resolve the project risks associated with the client's evolving requirements requiring careful change request management. Less time is required for integration as the process of integration goes on throughout the software development life cycle and the development time required is less due to using of components over and over. RUP involves The client’s in The system development process, so the result will be accordance with client wishes. The system built is expected to make it easier for employees to manage patient data from anywhere and anytime.